Nutritional value of a dry soluble gerodietetic product for enteral nutrition - Dmytro Antiushko; Tetiiana Bozhko; Nataliia Shapovalova; Mariia Fil; Tеtіana Brovenko; Galina Tolok; Artem Antonenko; Olga Gyrka; Mykhailo Bodak; Lubomyr Bezruchko (TECHNOLOGY CENTER PC®, 2021)
Results of conducted experimental studies of the nutritional value of the developed dry soluble gerodietetic product for enteral nutrition are presented. Content of proteins, fats, and carbohydrates (22.8, 11.8, and 56.4 g/100 g of dry product, respectively) was determined and calorific value (422.8 kcal/100 g) and mass fraction of macronutrients in it were calculated (21.5/25.1/53.4 respectively). Their compliance with recommendations of specialists to satisfy nutritional needs of older people, in particular, those with increased physical and neuro-emotional loads, certain dysfunctions, somatic diseases, injuries, and recovering after them were analyzed and determined. Qualitative and quantitative amino acid composition of the product was studied, the rate of its essential and conditionally essential amino acids was calculated on its basis, coefficient of discrepancy of its amino acid composition was found (17.14 %) and biological value of the protein component (82.86 %) was calculated. Experimental studies of the vitamin value of the developed product and its elemental structure were carried out. The dry product has a fairly high content of vitamins (especially ascorbic acid, retinol, thiamine, pyridoxine) and mineral elements (potassium, calcium, phosphorus, magnesium, iron, iodine, selenium). Based on the obtained results, an average level of satisfaction of the daily need for the studied vitamins (on average within 14–41 %), mineral elements (mostly by 10–25 %) from consumption of 100 g of dry product in the prepared liquid state was calculated. The conducted studies have shown high nutritional value, in particular calorific and biological value of the product and conformity of its composition to the needs of the older age groups
Eastern-European Journal of Enterprise Technologies. − Vol. 5 № 11 (113)-2021.
Keywords: product for enteral nutrition; dry soluble product; gerodietetic purpose; nutritional value